Spruce Balm-Based Semisolid Vehicles for Wound Healing: Effect of Excipients on Rheological Properties and Ex Vivo Skin Permeation - Eichenauer, Elisabeth; Jozić, Martina; Glasl, Sabine; Klang, Victoria (Pharmaceutics, 2023)
The treatment of chronic wounds, an important issue with the growing elderly population, is increasingly hindered by antibiotic resistance. Alternative wound care approaches involve the use of traditional plant-derived remedies, such as purified spruce balm (PSB), with antimicrobial effects and the promotion of cell proliferation. However, spruce balm is difficult to formulate due to its stickiness and high viscosity; dermal products with satisfying technological properties and the scientific literature on this topic are scarce. Thus, the aim of the present work was to develop and rheologically characterize a range of PSB-based dermal formulations with different hydrophilic/lipophilic compositions. Mono- and biphasic semisolid formulations based on different compounds (petrolatum, paraffin oil, wool wax, castor oil, and water) were developed and characterized by their organoleptic and rheological measurements. A chromatographic method of analysis was established, and skin permeation data were collected for pivotal compounds. The results showed that the dynamic viscosity ranged from 10 to 70 Pas at 10/s for the different shear-thinning systems. The best formulation properties were observed for water-free wool wax/castor oil systems with 20% w/w PSB followed by different water-in-oil cream systems. Skin permeation through porcine skin was observed for different PSB compounds (e.g., pinoresinol, dehydroabietic acid, and 15-hydroxy-dehydroabietic acid) using Franz-type diffusion cells. The permeation potential of wool wax/castor oil- and lard-based formulations was shown for all the analyzed substance classes. The varying content of pivotal compounds in different PSB batches collected at different timepoints from different spruce individuals might have contributed to observed differences in vehicle performance.